Clinical and Economic Impact of Early Diagnosis of Chronic Kidney Disease in General Practice: The Endorse Study - Pesce F; Bruno GM; Colombo GL; Di Matteo S; Maurizi AR; Mongelli V; Mele S; Narici L; Bianchi S; Bonomini M; Castellano G; De Nicola L; et al. (Dove Medical Press, 2024)
Francesco Pesce,1 Giacomo Matteo Bruno,2 Giorgio Lorenzo Colombo,2 Sergio Di Matteo,3 Anna Rita Maurizi,4 Valentina Mongelli,4 Silvia Mele,5 Lavinia Narici,5 Stefano Bianchi,6 Mario Bonomini,7 Giuseppe Castellano,8 Luca De Nicola,9 Giovanni Gambaro,10 Giuseppe Grandaliano,11 Gaetano La Manna,12 Antonello Pani,13 Andrea Ranghino,14 Loreto Gesualdo15 1Division of Renal Medicine, "Fatebenefratelli Isola Tiberina-Gemelli Isola", Rome, 00186, Italy; 2Department of Drug Sciences, University of Pavia, Pavia, Italy; 3S.A.V.E. Studi Analisi Valutazioni Economiche, Milan, Italy; 4Cardiovascular, Renal and Metabolism Medical Affairs, AstraZeneca, Milan, Italy; 5Value & Access, AstraZeneca, Milan, Italy; 6Nephrology and Dialysis Unit, Department of Internal Medicine, ASL Toscana Nordovest, Regione Toscana, Livorno, Italy; 7Department of Medicine, Section of Nephrology and Dialysis, G. D'Annunzio University, Chieti, 66013, Italy; 8UOC of Nephrology, Dialysis, and Kidney Transplant, IRCCS Foundation Ca' Granda Ospedale Maggiore Policlinico, Milan, Italy; 9Department of Advanced Medical and Surgical Sciences, Nephrology and Dialysis Unit, University Vanvitelli, Naples, Italy; 10Division of Nephrology and Dialysis, Department of Medicine, University of Verona, Verona, Italy; 11Department of Translational Medicine and Surgery, Università Cattolica Sacro Cuore, Rome, Italy; 12Nephrology Dialysis and Kidney Transplant Unit, IRCCS Azienda Ospedaliero-Universitaria Di Bologna, Bologna, Italy; 13Department of Nephrology and Dialysis, G. Brotzu Hospital, Cagliari, Italy; 14Nephrology, Dialysis and Kidney Transplant Unit, Ospedali Riuniti Ancona, Ancona, Italy; 15Nephrology, Dialysis and Transplantation Unit, Department of Precision and Regenerative Medicine and Ionian Area (Dimepre-J), University of Bari "aldo Moro", Bari, ItalyCorrespondence: Giorgio Lorenzo Colombo, Email colombog@unipv.itIntroduction: The underdiagnosis of chronic kidney disease (CKD) remains a significant public health concern. The Early chroNic kiDney disease pOint of caRe Screening (ENDORSE) project aimed to evaluate the clinical and economic implications of a targeted training intervention for general practitioners (GPs) to enhance CKD awareness and early diagnosis.Methods: Data on estimated Glomerular Filtration Rate (eGFR) and Urinary Albumin-Creatinine Ratio (uACR) were collected by 53 Italian GPs from 112,178 patients at baseline and after six months. The intervention involved six months of hybrid training provided by 11 nephrologists, which included formal lectures, instant messaging support, and joint visits for complex cases.Results: The results demonstrated a substantial increase in the use of eGFR (+44.7%) and uACR (+95.2%) tests. This led to a 128.9% rise in the number of individuals screened for CKD using the KDIGO classification, resulting in a 62% increase in CKD diagnoses. The intervention's impact was particularly notable in high-risk groups, including patients with type 2 diabetes, hypertension, and heart failure.Discussion: A budget impact analysis projected cumulative five-year savings of € 1.7 million for the study cohort. When these findings were extrapolated to the entire Italian CKD population, potential savings were estimated at € 106.6 million, highlighting significant cost savings for the national health service. The clinical simulation assumed that early diagnosed CKD patients would be treated according to current indications for dapagliflozin, which slows disease progression.Conclusion: The ENDORSE model demonstrated that targeted training for GPs can significantly improve early CKD detection, leading to better patient outcomes and considerable economic benefits. This approach shows promise for broader implementation to address the underdiagnosis of CKD on a national and potentially international scale. Keywords: eGFR, uACR, awareness, chronic kidney disease, general practice, economic impact, training intervention, early diagnosis